If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(4 + -1x) + 3(x + -5) = 9x (4 * 7 + -1x * 7) + 3(x + -5) = 9x (28 + -7x) + 3(x + -5) = 9x Reorder the terms: 28 + -7x + 3(-5 + x) = 9x 28 + -7x + (-5 * 3 + x * 3) = 9x 28 + -7x + (-15 + 3x) = 9x Reorder the terms: 28 + -15 + -7x + 3x = 9x Combine like terms: 28 + -15 = 13 13 + -7x + 3x = 9x Combine like terms: -7x + 3x = -4x 13 + -4x = 9x Solving 13 + -4x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 13 + -4x + -9x = 9x + -9x Combine like terms: -4x + -9x = -13x 13 + -13x = 9x + -9x Combine like terms: 9x + -9x = 0 13 + -13x = 0 Add '-13' to each side of the equation. 13 + -13 + -13x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -13x = 0 + -13 -13x = 0 + -13 Combine like terms: 0 + -13 = -13 -13x = -13 Divide each side by '-13'. x = 1 Simplifying x = 1
| 47-7=21 | | yfor-5x+4y=14 | | -4b-16-16=-56 | | 40-3n=-2(7n-1)-8n | | 47-7= | | 3x+2-x+6=-6 | | (2x+x^2)(x-2)=0 | | 11x-y=11 | | 3[20-4]= | | 2x^2-4x+x^3-2x^2=0 | | -7y+5(y-7)=-31 | | ln(x)=ln(2)+ln(x-3) | | log(x+3)+log(x+4)=log(x^3+13x^2)-log(x) | | 10+10*10-10= | | n+5ifn=2 | | 9x-3(5-x)=81 | | 10m^2-15mn+4mn-6n^2=0 | | p=0.4 | | -7u+4(u+2)=22 | | y+6=2y-6 | | 5(v-8)=3v-38 | | 8(x+18)=5(x+78) | | x=0.001q | | 3+p=25 | | -18t+26=-19 | | 12-11z=-(-9z-4) | | 0=128x^3-776 | | h(x)=-x^2-6x | | 7x+3-9x=-13 | | -9a-4b=-56 | | -7+4(u+2)=22 | | (3*2-5)+(-2*2+3)= |